Political dimensions of climate change adaption: Conceptual reflections and African examples = Dimensions politiques de l'adaptation au changement climatique - Irit Eguavoen; Karsten Schulz; Sara de Wit; Florian Weisser; Detlef Müller-Mahn (University of Bonn, Center for Development Research (ZEF), 2013)
This paper supports the argument that social science research should focus on adaptation to climate change as a social and political process, by analyzing the politics and interests of actors in climate change adaptation arenas, and by acknowledging the active role of those people who are expected to adapt. Most conventional climate research depoliticizes vulnerability and adaptation by removing dominant global economic and policy conditions from the discussion. Social science disciplines, if given appropriate weight in multidisciplinary projects, contribute important analyses by relying on established concepts from political science, human geography, and social anthropology. This paper explains relevant disciplinary concepts (climate change adaptation arena, governance, politics, perception, mental models, weather discourses, risk, blame, travelling ideas) and relates them to each other to facilitate the use of a common terminology and conceptual framework for research in a developmental context.
Keywords: 330; climate change adaptation arena; governance; politics; perception; mental models; weather discourse; risk; blame; travelling ideas; discourse; development; Africa; teaching material